Acute Myocardial Infarction in Hyperglycemic Patients with Undiagnosed Diabetes Mellitus. A Clinical Study - Shujaat Ali, Muhammad Mukarram, Ahmad Raza, Hafsa Jameel, Muhammad Abdullah Bambal, Naveed Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
Study Design: Current study was conducted from February,2022 to May, 2022 at Emergency, Medical and Cardiological units of The University of Lahore Teaching Hospital Lahore. The aims and objectives of this study was to identify the frequency rate of myocardial infraction in diabetic type-2 patients. Materials and Methods: Sample size: Total 125 individuals were selected for current study, and divided them into three different groups. In Group-A 25 normal individuals, while in Group-B 20 non-diabetic patients with myocardial infraction. Where as in Group-C 80 patients were diabetic with myocardial infraction were selected respectively. Biomarkers: Blood-glucose level, Systolic and Diastolic blood pressure, Troponin I - levels, ECG. Presentation of Data: The collected raw data were bio statistically presented through SPSS version 2020.Variation within the groups were elaborated with the application of mean standard deviation and significant changes were considered according to the (P<0.05). Results: The findings of current study were significant(P<0.05) and a remarkable change in blood glucose level, Systolic and Diastolic blood pressure, Troponin I - levels, ECG of group-B (140.0±0.01, 160±0.03, 90±0.03, 0.07±0.01) and group-C (250.2±0.02, 195±0.02, 105±0.02, 0.20±0.01) were measured and compared with group-A (138.0±0.01, 120±0.01, 75±0.01, 0.03±0.00) respectively. Conclusion: In acute myocardial infarction high blood glucose levels are typical and are linked to a higher risk of mortality in diabetic patients than non-diabetic patients.